Electrospray ionization deposition of ultrathin ionic liquid films: [C 8C1Im]Cl and [C8C1Im][Tf 2N] on Au(111) - Rietzler, Florian; Piermaier, Marius; Deyko, Alexey; Steinrück, Hans-Peter; Maier, Florian (Langmuir, 2014)
We introduce a new method for preparing ultrathin ionic liquid (IL) films on surfaces by means of electrospray ionization deposition (ESID) under ultraclean and well-defined ultra-high-vacuum (UHV) conditions. In contrast to physical vapor deposition (PVD) of ILs under UHV, ESID even allows deposition of ILs, which are prone to thermal decomposition. As proof of concept, we first investigated ultrathin [CCIm][TfN] (=1-methyl-3-octyl imidazolium bis(trifluoromethyl)imide) films on Au(111) by angle-resolved X-ray photoelectron spectroscopy (ARXPS). Films obtained by ESID are found to be virtually identical to films grown by standard PVD. Thereafter, ESID of [CCIm]Cl on Au(111) was studied as a first example of an IL that cannot be prepared as ultrathin film otherwise. [C CIm]Cl forms a wetting layer with a checkerboard arrangement with the cationic imidazolium ring and the chloride anion adsorbed next to each other on the substrate and the alkyl chain pointing toward vacuum. This arrangement within the wetting layer is similar to that observed for [CCIm][TfN], albeit with a higher degree of order of the alkyl chains. Further deposition of [CC Im]Cl leads to a pronounced island growth on top of the wetting layer, which is independently confirmed by ARXPS and atomic force microscopy. This behavior contrasts the growth behavior found for [CC Im][TfN], where layer-by-layer growth on top of the wetting layer is observed. The dramatic difference between both ILs is attributed to differences in the cation-anion interactions and in the degree of order in the wetting layer of the two ILs. © 2014 American Chemical Society.